The Effectiveness of Food and Health Services for the Correctional Assisted Residents of The Pasangkayu Class IIB Detention Center - Ika Darmawati (Journal of Health Literacy and Qualitative Research, 2024)
In Article 14 letter d of Law Number 12 of 1995, concerning Correctional Services, it states that "Assisted citizens have the right to get proper health and food services". This can lead to or foster a sense of wanting to do good, foster an attitude that is more responsive to their needs and provides protection for the rights of the fostered citizens. This study aims to determine the effectiveness of food and health services for WBP in the Class IIB Pasangkayu Detention Center. The research carried out is a type of descriptive research with qualitative methods or approaches. In this study, determining informants using purposive sampling techniques, that is, selected with certain considerations and goals, which really master an object that the researcher is researching. Researchers also used Triangulation as a technique to check the validity of the data. Triangulation is carried out using different techniques, namely interviews, observations and documents. The results showed that the implementation of food and health services for the assisted residents in the Class IIB Pasangkayu detention center had met the indicators of productivity, responsiveness, resposibility, and accountability. However, in carrying out these services, there are still some obstacles faced by the officers so that it gives the impression to the assisted residents that there are some things about food and health services that are not optimal. The conclusion of this study is that food and health services for residents assisted by the class IIB Pasangkayu detention center are running effectively. It is hoped that related parties can improve the quality of food and health services to all assisted residents.